Pameran Seni Kontemporer Dalam Kemas Imaji Surealis Sebagai Wadah Masyarakat Penikmat Seni di Kota Malang - Budiyanto, Budiyanto; Ibrahim, Muh. Maulana Malik; Afnani, Rizal (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2024)
The arts in the city of Malang are so very diverse as well as the artists who continue to be creative in their work until now, to become a culture or culture in the city itself. Contemporary art often emphasizes ideas and concepts over technical skills alone, some works can appear more conceptually complex than visual. There is no single style or approach in contemporary art. Therefore, there is a need for a creative forum that combines all elements of art in the city of Malang. The purpose of this service is to create a forum for art creation in the form of art exhibitions for all artists in the city of Malang by developing the concept of works on contemporary art, as well as providing art connoisseurs related to education on the development of contemporary art to date, and providing new aesthetic experiences to the community. The contemporary art exhibition with the title Fenomeart in surreal image packaging is an attractive forum for art connoisseurs in Malang City. The following are some of the steps or methods that will be taken to organize an art exhibition, including determining the concept and theme, selecting artworks, determining the strategic location of the exhibition, promotion involving mass media, curatorial as well as educating the community, involvement of the art community in the city of Malang, security of artworks, and feedback from the public.